2020
DOI: 10.5343/bms.2019.0079
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton composition in the subtropical coastal shelf environment of Cape Canaveral, Florida

Abstract: The abundance and composition of the phytoplankton community off the coast of Cape Canaveral, Florida was examined from Fall 2013 to Summer 2015. The region is a shallow shelf environment. Water samples were collected quarterly at 24 sites from the surface and bottom of the water column; temperature and nutrient concentrations were determined. Photoautotrophic picoplanktonic prokaryotes were consistently important in terms of numerical abundance and biomass throughout the study. Among the cyanobacteria, a surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The study showed that ciliates on average represent over a third of total zooplankton biomass. The same study also showed that picoand nano-phytoplankton taxa represented on average over 50% of total phytoplankton biomass (Tate et al, 2020). Since ciliates are known to be a 10.…”
Section: Top-down Control and Other Issuesmentioning
confidence: 74%
See 1 more Smart Citation
“…The study showed that ciliates on average represent over a third of total zooplankton biomass. The same study also showed that picoand nano-phytoplankton taxa represented on average over 50% of total phytoplankton biomass (Tate et al, 2020). Since ciliates are known to be a 10.…”
Section: Top-down Control and Other Issuesmentioning
confidence: 74%
“…Mean TN levels often remained between 0.1-0.25 mg L −1 . Notably, the high levels of TN in the fall of 2013 coincided with a bloom of the nitrogen-fixing cyanobacterium Trichodesmium erythraeum (Tate et al, 2020). Mean total phosphorus concentrations ranged from 0.007 ± 0.001 mg L −1 to 0.033 ± 0.004 mg L −1 in summer 2018 and in spring 2015, respectively, (Figure 7).…”
Section: Total Nitrogen and Phosphorusmentioning
confidence: 99%